2014
DOI: 10.1111/ajco.12177
|View full text |Cite
|
Sign up to set email alerts
|

EGFRgene mutations in patients with adenosquamous lung carcinoma

Abstract: EGFR gene mutations in ADSQ carcinoma patients may be more common than previously thought. EGFR mutation testing is appropriate in ADSQ-bearing patients, in which response for molecular-based therapy is predictable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
1
8
0
1
Order By: Relevance
“…The observed prevalence (21.5%) of EGFR mutations in patients with ASC was consistent with that reported in previous studies (13–44%, Table S2) . We and others found that EGFR ‐mutated cells were distributed in both AC and SCC components of ASC specimens.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The observed prevalence (21.5%) of EGFR mutations in patients with ASC was consistent with that reported in previous studies (13–44%, Table S2) . We and others found that EGFR ‐mutated cells were distributed in both AC and SCC components of ASC specimens.…”
Section: Discussionsupporting
confidence: 91%
“…The observed prevalence (21.5%) of EGFR mutations in patients with ASC was consistent with that reported in previous studies (13-44%, Table S2). [5][6][7][8][9][10][11][12][13] We and others found that EGFR-mutated cells were distributed in both AC and SCC components of ASC specimens. In a case report and series analyses, patients with EGFR mutations in ASC specimens responded to EGFR-TKI therapy with an overall response rate of 88%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data might not have been adequately discussed due to the limited series as well as the possibility of taking adenosquamous carcinoma samples lacking the adenocarcinoma component as causes of bias. Few recent papers deemed the possibility that EGFR mutations are more common than expected in adenosquamous carcinoma [32]. …”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps the reason why the mutations found in squamous cell carcinomas are far more frequent than those reported by other authors whose studies have been conducted on an adequate number of cases. 10,11,19 The considerable discrepancy in the reported data could be due to differences in the methodology of performing the mutation analysis, but could be also a result of genetic differences between eastern patient populations and other populations. 7 Such ethnic diversity can be found, to a certain extent, in Southern Bulgaria, which makes it necessary to compare these data with data from other regions of the country.…”
Section: Introductionmentioning
confidence: 99%